A Comparative Review of the Open Source Data Integration Tools - Pall, Amanpartap Singh; Khaira, Jaiteg Singh (Gyan Management Journal, 2013)
The organization dealing with voluminous data has two options, either to build its own ETL tool or buy : w from the market. Extraction-Transformation-Loading {ETL) tools are specialized tools diat deal .-:ith data warehouse homogeneity, cleaning and loading problems. Selecting an ETL tool has always :ieen a tedious task as one wrong choice would incur in huge losses of resources, time and money. The Jrganization however, has few options either to go in for some known closed source commercial tool or go in for an open source tool. In this paper, we have attempted to compare and evaluate the leading open source ETL tools. The choice of the tools has been done by looking at the vendors and survey reports discussions and disclosures on key features incorporated in them.
Keywords: Data Integration; ETL; ETL tools; Open Source ETL Tools